2015
DOI: 10.1210/en.2015-1141
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-β Up-Regulates IGF1R Expression and Activity to Inhibit Apoptosis and Increase Growth of Medulloblastoma

Abstract: Medulloblastoma (Med) is the most common malignant brain tumor in children. The role of ESR2 [estrogen receptor (ER)-β] in promoting Med growth was comprehensively examined in three in vivo models and human cell lines. In a novel Med ERβ-null knockout model developed by crossing Esr2(-/-) mice with cerebellar granule cell precursor specific Ptch1 conditional knockout mice, the tumor growth rate was significantly decreased in males and females. The absence of Esr2 resulted in increased apoptosis, decreased B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Considering the progressive nature of MB development in Ptch1 +/- , the apparent increased sensitivity of females to dysregulated SHH signaling could be related to the increased levels of circulating estrogens in mature females. These activities of estrogen are mediated through modulation of rapid estrogen signaling, estrogen receptor-regulated gene expression, and resulting modulation of growth factor-related signal transduction pathways (Cookman and Belcher, 2015; Garcia-Segura et al, 2006). Increased activation of ERβ signaling increases GCP mitogenesis and migration, and upregulates neuroprotective mechanisms in mature granule cells, which also act in the etiology and progression of MB to drive tumor progression (Belcher, 2008; Cookman and Belcher, 2015; Guillette et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the progressive nature of MB development in Ptch1 +/- , the apparent increased sensitivity of females to dysregulated SHH signaling could be related to the increased levels of circulating estrogens in mature females. These activities of estrogen are mediated through modulation of rapid estrogen signaling, estrogen receptor-regulated gene expression, and resulting modulation of growth factor-related signal transduction pathways (Cookman and Belcher, 2015; Garcia-Segura et al, 2006). Increased activation of ERβ signaling increases GCP mitogenesis and migration, and upregulates neuroprotective mechanisms in mature granule cells, which also act in the etiology and progression of MB to drive tumor progression (Belcher, 2008; Cookman and Belcher, 2015; Guillette et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These activities of estrogen are mediated through modulation of rapid estrogen signaling, estrogen receptor-regulated gene expression, and resulting modulation of growth factor-related signal transduction pathways (Cookman and Belcher, 2015; Garcia-Segura et al, 2006). Increased activation of ERβ signaling increases GCP mitogenesis and migration, and upregulates neuroprotective mechanisms in mature granule cells, which also act in the etiology and progression of MB to drive tumor progression (Belcher, 2008; Cookman and Belcher, 2015; Guillette et al, 2018). It is possible that the more sever phenotypes detected in Ptch1 +/- female mice are related to a relative increase in estrogen signaling in ERβ positive Ptch1 +/- granule cell-like precursors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen receptors play an important role in the regulation of numerous metabolic and proliferative processes, including tumorigenesis, preferentially through interaction with specifi c response element in the target genes (Mueller et al 2000;Cookman and Belcher 2015;Lau and To 2016;Ur Rahman and Cao 2016;Wesolowska et al 2016;Zhu et al 2016). Estrogen receptors are responsible for the regulation of cell growth and apoptosis as well as are involved, at least partly, in the development, proliferation, and progression of some cancers.…”
mentioning
confidence: 99%
“…At the same time, Li et al (2013) have shown that in U87 cells estrogen receptors inhibit the cell proliferation and reduced cells in the S+G2/M phase and that hypoxia induced estrogen receptor-β5 expression in glioma as a self-protective mechanism against tumor proliferation. Recently, Cookman and Belcher (2015) have demonstrated that estrogen promotes medulloblastoma growth through estrogen receptor-β-mediated increases in IGF1R expression and activity, which induce cytoprotective mechanisms that decrease apoptosis.…”
mentioning
confidence: 99%